Formation and reactions of alkyl adamantanes in sediments: Carbon surface reactions - Berwick, Lyndon; Alexander, Robert; Pierce, Kieran (Pergamon, 2011)
Diamondoids are hydrocarbons with a carbon skeleton that is superimposable on the diamond lattice. Adamantane is the cage-shaped primary unit of diamondoids and occurs widely in sediments and petroleum. The first report of adamantane isolated from petroleum extends back seven decades, but the precursors and reaction mechanisms for the formation of adamantane and related diamondoids in sediments has remained unclear. We report the formation of alkyl adamantanes by heating beta-ionone with activated carbon in closed system pyrolysis experiments in the range 170-320 C. In addition, hydrogen exchange, demethylation, methyl transfer and isomerisation reactions were observed when the model compounds adamantane and 1,3-dimethyladamantane were heated at moderate temperature with activated carbon. A reaction pathway for the formation and reactions of alkyl adamantanes is proposed on the basis of ring isomerisation of adamantane to protoadamantane on the activated carbon surface. The carbonaceous surface reactions described help account for the occurrence and distribution of alkyl adamantanes in petroleum basins, as evidenced by the strong linear relationships between compound pairs related by isomerisation and demethylation for a set of crude oils from the Carnarvon Basin, Western Australia.